Enhancing Employee Performance through Education, Training, Motivation, and Work Discipline in Tanah Bumbu (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
Employee performance is a crucial factor in supporting the effectiveness of internal government supervision. As a Government Internal Supervisory Apparatus (APIP), the Regional Inspectorate plays a strategic role in ensuring accountability, transparency, and effectiveness in public governance. However, increasing organizational demands and the complexity of supervisory responsibilities require employees to possess adequate competencies, strong work motivation, and high levels of work discipline to achieve optimal performance. This study aims to examine the effects of education and training, work motivation, and work discipline on employee performance at the Regional Inspectorate of Tanah Bumbu Regency. A quantitative approach with a survey method was employed in this study. Data were collected through questionnaires distributed to all research respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that education and training, work motivation, and work discipline have positive and significant effects on employee performance. Furthermore, these variables collectively contribute substantially to performance improvement. The results suggest that continuous human resource development through education and training programs, strengthening employee motivation, and maintaining consistent work discipline are essential factors in enhancing employee performance at the Regional Inspectorate of Tanah Bumbu Regency. Keywords: : education and training; work motivation; work discipline; employee performance; regional inspectorate